2016
DOI: 10.1155/2016/5750672
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness-Displacement Correlation from the RC Shear Wall Tests of the SAFE Program: Derivation of a Capacity Line Model

Abstract: The response of 13 reinforced concrete shear walls submitted to successive seismic tests has been postprocessed to produce time histories of secant stiffness and displacement oscillation amplitude. For every wall an envelope curve of displacement amplitude versus stiffness is identified which is fairly modelled by a straight line in double logarithmic scale. This relatively simple model, when used as a capacity line in combination with the demand response spectrum, is able to predict in an approximate manner t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The experimental curves available are the ones associated to the PsD tests only. These results were analyzed to get a series of EVD curves (see Molina et al for details on the procedure used), as shown in the succeeding part of the paper. If adopting the experimental EVD curve, which is characterized by a larger EVD in the displacement region of interest, the performance point is found at a sensibly low value along the capacity curve, which is also in accordance with the experimental observation.…”
Section: Application Of the Csm And Comparison With Results Of Pseudomentioning
confidence: 99%
See 3 more Smart Citations
“…The experimental curves available are the ones associated to the PsD tests only. These results were analyzed to get a series of EVD curves (see Molina et al for details on the procedure used), as shown in the succeeding part of the paper. If adopting the experimental EVD curve, which is characterized by a larger EVD in the displacement region of interest, the performance point is found at a sensibly low value along the capacity curve, which is also in accordance with the experimental observation.…”
Section: Application Of the Csm And Comparison With Results Of Pseudomentioning
confidence: 99%
“…The method proposed by Molina et al to determine the EVD factors directly from the results of PsD tests brings to the curves reported in Figure 11 in comparison with those obtained from cyclic tests. Moreover, Molina et al use a capacity line obtained from the PsD results as well, which should match the RS spectrum in the ADRS representation. Such capacity line is derived from the simultaneous identification of linear stiffness and damping properties and is necessary to avoid the need of cyclic tests or any numerical simulations.…”
Section: Considerationsmentioning
confidence: 86%
See 2 more Smart Citations
“…Nonlinear seismic response of walls coupled with steel and concrete beams was also investigated [4][5][6]; the research demonstrated the advantages of using steel beams to couple reinforced concrete walls. Experiments and simulations have been conducted on the joints of steel CBs and shear walls [7][8][9][10][11], and the results demonstrated that the anchorage has important impacts on the stiffness degradation; the shear yield style steel CB has excellent ductility performance and energy performance, construction convenient, and easy maintenance and replacement, and especially the maintenance can be easily replaced after the earthquake. Wu [12] investigated the steel CB and concrete shear wall joints by employing experiments and finite element analysis, the failure mode of joints, strain distribution, bearing capacity, CB size, concrete strength, ductility, and hysteretic behaviors were studied.…”
Section: Introductionmentioning
confidence: 99%